Vol 13 No 1 (2019) KUALITAS LAYANAN DAN SACRIFICE UNTUK MEMBENTUK PERCEIVED VALUE DARI KEPUASAN PELANGGAN UNTUK MEMPERKUAT PURCHASE DIINTENTION DAN INFORMASI LAYANAN TELKOM PELANGGAN KORPORASI - Suratman Malik; Syaiful Syaiful (Cakrawala Akuntansi & Manajemen, 2019)
The aim of the research is to investigate the influence of service quality and sacrifice on customer perceived value and customer satisfaction on purchase intention either partially or simultaneously. The variables influencing purchase intention are service quality, sacrifice, customer perceived value, and customer satisfaction. The populations were Telkom corporate customers in the working area of Eastern part of Indonesia involving customers in the sub area of Makassar, Palu, Menado,Bali, and West East Nusatenggara, sub area of Papua and Maluku. The selection of simple used Yamane Osida Takesih with the error standard level of 5%, so the selected simple consisted of 302 respondents, Meanwhile, the model used in the research was structural equation modeling (SEM) to find out the cusal relationship among the affecting variables in that model. The results of the research reveal that service quality of Telkom service product base don the value given by the customers is good.Among all indication, ROPMIS forms service quality, image indicator of Telkom corporate has the best value, while the lowest value indicator, which has agood category, is management indicator. The result of the research related to the influence of inter-variable are : Service quality and sacrifice variable have a positive and significant influence on customer perceived value variable, Service quality, scarifice, and customer perceived value variable have a positive and significant influence on customer satisfaction variable, Customer perceived value, and customer satisfaction have a positif and significant influence on purchase intention variable, Service quality, sacrifice, customer perceived value and customer satisfaction have a positive and significant influence on purchase intention variable.